Perawatan Pipa untuk Persawahan Limpok Kabupaten Aceh Besar - Masri Ali; Tajuddin; Iskandar; Akhyar; Syahriza; Husaini; Izarul Machdar (Yayasan Kawanad, 2023)
Charity activities in Limpok Village, Aceh Besar District, Darussalam District, Aceh State. This activity was carried out because there is a small river in the village and the water is not yet available as a source of water for the rice fields. The purpose of this activity is to obtain and distribute rice water to increase farmers' yields. As for the stage of activities, we hold round-table discussions with local residents about the water demand of paddy fields, investigate the locations of PVC pipes, and work with local residents to lay PVC pipes. This activity demonstrates the great enthusiasm of residents to participate in a series of community service activities. As a result of this activity, we succeeded in pumping up water from a small river to the rice fields, which had previously depended on rainwater. This charity should therefore serve as an example for other villages with similar problems and demonstrate the importance of cooperation between communities and government agencies in building and improving the quality of life in the region.